2016
DOI: 10.1155/2016/3160247
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Ferulic Acid and Z‐Ligustilide, Major Components of A. sinensis, on Regulating Cold‐Sensing Protein TRPM8 and TPRA1 In Vitro

Abstract: Angelica sinensis has been used to attenuate cold-induced cutaneous vasospasm syndrome, such as Raynaud's disease and frostbite, in China for many years. Ferulic acid (PubChem CID: 445858) and Z-ligustilide (PubChem CID: 529865), two major components extracted from Angelica sinensis, had been reported to inhibit vasoconstriction induced by vasoconstrictors. In this study, the pharmacological interaction in regulating cold-induced vascular smooth muscle cell contraction via cold-sensing protein TRPM8 and TRPA1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…Thus, it is likely that the ER sub-population of TRPA1 selectively drives the ERS responses observed following treatment with WSPM and other TRPA1 agonists. It is also possible that cell surface TRPA1 activation may promote ER calcium release through other ER calcium release channels such as ryanodine receptors and/or IP3 receptors, as suggested by others (Pan et al, 2016;Xu et al, 2017), to promote ERS. The finding that AITC-driven calcium flux in HBEC cells was only partially inhibited by thapsigargin pre-treatment, but extensively inhibited by EGTA and ruthenium red supports such a possibility.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, it is likely that the ER sub-population of TRPA1 selectively drives the ERS responses observed following treatment with WSPM and other TRPA1 agonists. It is also possible that cell surface TRPA1 activation may promote ER calcium release through other ER calcium release channels such as ryanodine receptors and/or IP3 receptors, as suggested by others (Pan et al, 2016;Xu et al, 2017), to promote ERS. The finding that AITC-driven calcium flux in HBEC cells was only partially inhibited by thapsigargin pre-treatment, but extensively inhibited by EGTA and ruthenium red supports such a possibility.…”
Section: Discussionmentioning
confidence: 94%
“…Under tissue damage conditions, increased ROS stimulates the channel activities of TRPA1 to mediate increases in cytosolic Ca 2+ in ISCs (Figure 8B). As for RyR, besides its potential to directly sense ROS, it is known to act synergistically with TRPA1 in a positive feedback mechanism to release more Ca 2+ from the ER into the cytosol upon sensing the initial Ca 2+ influx through TRPA1 (Pan et al, 2016).
10.7554/eLife.22441.036Figure 8.Connection between ROS, intracellular calcium, and stem cell activity.( A ) Under tissue homeostasis conditions, basal levels of ROS and other unidentified stimuli can activate TRPA1 and RyR channels at low levels to allow low levels of cytosolic Ca 2+ , autocrine EGFR ligand Spi, and Ras/MAPK activity required for stem cell self-renewal and minimal level of proliferation.
…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ligustilide showed a good analgesic activity, which inhibited the activation of JNK/ c-Jun in spinal cord caused by complete freudian adjuvant (CFA) [26], reduced the in ammatory pain of spinal astrocytes after CFA peripheral injection [27], suppressed microglia cells to mediate in ammatory pain [28]. Other studies reported that ferulic acid and ligustilide could achieve the therapeutic effect on cold-induced vasospasm through the combined action of TRPM8 and TPRA1 [29], which might also be a mechanism for the analgesic effect of the fth extract. Thus, the increase in these components could explain the better integrated therapeutic effect of the fth extract on mice with UC.…”
Section: Discussionmentioning
confidence: 99%